2018
DOI: 10.1021/acschembio.7b01048
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Pederin Family Compound in a Nonsymbiotic Bloom-Forming Cyanobacterium

Abstract: The pederin family includes a number of bioactive compounds isolated from symbiotic organisms of diverse evolutionary origin. Pederin is linked to beetle-induced dermatitis in humans, and pederin family members possess potent antitumor activity caused by selective inhibition of the eukaryotic ribosome. Their biosynthesis is accomplished by a polyketide/nonribosomal peptide synthetase machinery employing an unusual trans-acyltransferase mechanism. Here, we report a novel pederin type compound, cusperin, from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…We initiated our study on M. hentscheli with consideration to the possible enzymatic origin of its known natural products, the mycalamides, pateamines, and pelorusides. Mycalamides belong to the pederin family, a group of defensive polyketides produced in remarkably diverse host-symbiont systems comprising beetles (33), psyllids (34), lichens (35), and sponges (36,37) as well as free-living bacteria (38,39) with producers from at least four different phyla. We previously showed that the compounds from non-Mycale holobionts are enzymatically generated by a family of polyketide synthases (PKSs) termed trans-acyltransferase (trans-AT) PKSs (33,36,40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We initiated our study on M. hentscheli with consideration to the possible enzymatic origin of its known natural products, the mycalamides, pateamines, and pelorusides. Mycalamides belong to the pederin family, a group of defensive polyketides produced in remarkably diverse host-symbiont systems comprising beetles (33), psyllids (34), lichens (35), and sponges (36,37) as well as free-living bacteria (38,39) with producers from at least four different phyla. We previously showed that the compounds from non-Mycale holobionts are enzymatically generated by a family of polyketide synthases (PKSs) termed trans-acyltransferase (trans-AT) PKSs (33,36,40).…”
Section: Resultsmentioning
confidence: 99%
“…The identification of the mycalamide producer Entomycale ignis adds a further bacterial lineage to an already astonishing diversity of organisms producing pederin-type compounds, reinforcing intriguing questions about the evolution and dispersal of these natural products. Previously identified producers belong to alpha- (38), beta- (34) and gammaproteobacteria (33) as well as two Cyanobacteria (35,39) and Tectomicrobia (10), and they are mostly symbionts of unrelated hosts comprising sponges (10), beetles (33), psyllids (34), and a lichen fungus (35). The data support extensive horizontal gene transfer and retention in extraordinarily diverse host-symbiont systems, including intracellular organelle-like bacteria with minimalistic genomes (34) as well as multicellular prokaryotes featuring genomes of around 10 Mb (10,14).…”
Section: Leader --T I G I V V V I G a A V V A V A N T G A N A N A G Amentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the last two modules of SbnO, comprising distinctive tandem ECH and ACP domains, are absent in the glutaramide clusters from Streptomyces and Burkholderia genomes. Moreover, protein identity analysis of downstream SbnO domains revealed similarities with the pederin-family gene clusters of labrenzin (29), pederin (39,45), nosperin (46), and cusperin (47), as well as with the clusters of onnamide (48) and oocydin A (23). Tandem ACP domains present in all genomes play an important role in β -branching, assisting the HCS cassette (49).…”
Section: Comparative Analysis Of the Modular Organization Of Pks And mentioning
confidence: 99%
“…For 3.5 billion years, cyanobacteria have kept developing new adaptation features and defense mechanisms which allowed them to colonize the earth, shape its atmosphere from anoxic to oxygenic, and ever since to survive in harsh and strongly competitive environments under extreme temperatures, salt stress, high UV-radiation, and pathogen attack [1,2]. One of these survival strategies is the production of a vast variety of secondary metabolites, exhibiting a broad spectrum of biological activities and properties, including peptides, lipopeptides, polyketides, alkaloids, lipids, and terpenoids [3][4][5][6][7]. When growth conditions are advantageous, cyanobacteria proliferate, resulting in overgrown 2 of 12 populations known as cyanobacterial blooms (CBs), which can be harmful for aquatic life as well as for human health because of the toxins they produce [8,9].…”
Section: Introductionmentioning
confidence: 99%